Diversity in Hydrogen-rich Envelope Mass of Type II Supernovae. III. The Mass-loss and Evolutionary Pathways of the Red Supergiant Progenitors - Qiliang Fang; Takashi J. Moriya; Keiichi Maeda; Andris Dorozsmai; Javier Silva-Farfán (The Astrophysical Journal)
We present a comprehensive analysis of 32 type II supernovae (SNe II) with plateau phase photometry and late phase ( nebular ) spectroscopy available, aiming to bridge the gap between the surface and core of their red supergiant (RSG) progenitors. Using MESA + STELLA , we compute an extensive grid of SN II light-curve models originating from RSG with effective temperatures T _eff around 3650 K and hydrogen-rich envelopes artificially stripped to varying degrees. These models are then used to derive the hydrogen-rich envelope masses M _Henv for SNe II from their plateau phase light curves. Nebular spectroscopy further constrains the progenitor RSG’s luminosity log L _prog and is employed to remove the degeneracies in light-curve modeling. The comparison between log L _prog – M _Henv reveals that M _Henv spans a broad range at the same log L _prog , and almost all SNe II have lower M _Henv than the prediction of the default stellar wind models. We explore alternative wind prescriptions, binary evolution models, and the possibility of more compact RSG progenitors. Although binary interaction offers a compelling explanation for the nonmonotonicity and large scatter in the log L _prog – M _Henv relation, the high occurrence rate of partially stripped RSGs cannot be accounted for by stable binary mass transfer alone without fine-tuned orbital parameters. This highlights that, despite being the most commonly observed class of core-collapse SNe, SNe II likely originate from a variety of mass-loss histories and evolutionary pathways that are more diverse and complex than typically assumed in standard stellar evolution models.